Kemampuan Numerasi Pada Siswa Tunarungu - Benny Wahyudi (Jurnal Pendidikan Indonesia, 2022)
This study aims to determine and describe the numeracy skills of deaf students. The method used in this research is the Systematic Literature Review method. The research subjects in this case were high school-LB students. After going through the inclusion and quality test stages, the literature reviewed was 5 articles. The results and findings in the articles show that there are several indicators in describing numeracy skills. The indicators of numeracy ability in question are (1) being able to use various kinds of numbers and symbols related to basic mathematics to solve problems in various contexts of daily life, (2) Analyzing information displayed in various forms (graphs, tables, charts). , diagrams and so on), and (3) interpret the results of the analysis to predict and make decisions. With the intellectual results of deaf students there is no difference compared to students without hearing loss, but have a longer time in the learning process.